Micropeptide ASAP encoded by LINC00467 promotes colorectal cancer progression by directly modulating ATP synthase activity - Qiwei Ge; Dingjiacheng Jia; Dong Cen; Yadong Qi; Chengyu Shi; Junhong Li; Lingjie Sang; Luo-jia Yang; Jiamin He; Aifu Lin; Shujie Chen; Liangjing Wang (The Journal of Clinical Investigation, 2021)
Emerging evidence has shown that open reading frames inside long noncoding RNAs (lncRNAs) could encode micropeptides. However, their roles in cellular energy metabolism and tumor progression remain largely unknown. Here, we identified a 94 amino acid–length micropeptide encoded by lncRNA LINC00467 in colorectal cancer. We also characterized its conservation across higher mammals, localization to mitochondria, and the concerted local functions. This peptide enhanced the ATP synthase construction by interacting with the subunits α and γ (ATP5A and ATP5C), increased ATP synthase activity and mitochondrial oxygen consumption rate, and thereby promoted colorectal cancer cell proliferation. Hence, this micropeptide was termed ATP synthase–associated peptide (ASAP). Furthermore, loss of ASAP suppressed patient-derived xenograft growth with attenuated ATP synthase activity and mitochondrial ATP production. Clinically, high expression of ASAP and LINC00467 predicted poor prognosis of colorectal cancer patients. Taken together, our findings revealed a colorectal cancer–associated micropeptide as a vital player in mitochondrial metabolism and provided a therapeutic target for colorectal cancer.